HUBUNGAN PENGETAHUAN PELAYANAN PRIMA TERHADAP KUALITAS LAYANAN SISWA PENGELOLAAN USAHA KECANTIKAN DI SMK NEGERI 1 BERINGIN - Aritonang, Rohana (PELANGI PENDIDIKAN, 2015)
Abstract. The aim of this research is to find out prima service knowledge of the students of beauty business management at SMK Negeri 1 Beringin. To find out the quality service of students beauty business management SMK Negeri 1 Beringin. To find out the correlation between prima service knowladge to the quality service of students of beauty business management at SMK Negeri 1 Beringin. Research methodology used correlational research methodology. The sample in this research were the students of XII grade beauty skill program at SMK Negeri 1 Beringin that consist of 30 students. The variable of this research was prima service knowladge as the free variable (X) and prima service quality as the depending variable (Y). The research instruments used test and questionnaire. The test used to know the students knowladge about prima service and questionnaire used to know the students service quality. The data analysis and which used paametric experiment called product moment experiment which analysis requirement experiment that was normality test, linearity test and significance test of regression equation. From the result of data normality test the research found that for prima service data and for rima service quality data where so so both of them was distributed normality. Regretion equality Y to X was got that . The result of significance test of regression equation was got . It can be concluded that the regression coffecient means. Linierity test result got so it means linier regretion equality. The result of this research was the prima servie knowladge of the students XII grade beauty skill state SMK Negeri 1 Beringin was in the sufficient category. There was correlation between prima service knowladge to the students service quality at XII grade beauty skill state SMK Negeri 1 Beringin. This statement can be proved from the score of and score of where . Kata Kunci: Pengetahuan Pelayanan Prima, Kualitas Layanan Siswa.